Chemical Separation of Copper from the Printed Circuit Board of Dead Electronic Gadget Cell Phone Set (Samsung J-2) - Aryal, Geeta; Giri, Jyoti (Journal of Nepal Chemical Society, 2024)
The increasing popularity of electronic devices among the public has increased electronic waste (e-waste). Most electronic devices become obsolescent after their use and generate hazardous chemicals if not disposed properly. The conducting networks in all electronic gadgets are made up of Copper (Cu) that can be retrieved by the chemical segregated method. In this experiment, a hydrometallurgical technique was used as acid leaching, selective recovery of Cu from the leachate using the group separation methods and measured the Cu metal separated from the acid leach. 5.05 g CuO is extracted which is equivalent to 4.03 g of Cu from the Samsung J-2 cell phone having an initial weight of 18.33 g PCBs. Atomic Absorption Spectroscopy (AAS) and Energy Dispersed X-ray analysis (EDX) techniques are used for the characterization of the extract. The recovery of Cu from this technique is about 93 % of the PCB board of Samsung J-2 mobile set.